PENGARUH KREDIBILITAS, CITRA MEREK, DAN KEPERCAYAAN KONSUMEN TERHADAP MINAT BELI PRODUK MAKE OVER DALAM PEMASARAN OMORFO SHOP PADA SHOPEE DI MAKASSAR - Dwita Ansir, Ratna; Romadhoni, Buyung; Indrayani, Syarthini (Ekonomi & Bisnis, 2025)
This study analyzes the influence of credibility, brand image, and consumer trust on purchase intention for Make Over products at Omorfo Shop on Shopee in Makassar. Using a quantitative approach and multiple linear regression analysis, the sample consists of 130 respondents who are active consumers of Omorfo Shop. The results indicate that brand image and consumer trust have a significant effect on purchase intention, while credibility does not show a significant partial effect. Data were analyzed using SPSS version 29.Keywords: Credibility, Brand Image, Consumer Trust and Purchase Intention